Tight-binding studies of uniaxial strain in T-graphene nanoribbons. (24th May 2022) - Hopkinson, J; Hancock, Y
Abstract: The role of uniaxial strain in armchair, T-graphene nanoribbons (ATGNRs) with symmetric and asymmetric structures is investigated using a nearest-neighbour, tight-binding (TB) model. ATGNRs with structural symmetry and two a sub-lattice structure exhibit Dirac points at zero strain. Application of uniaxial strain to these systems induces multiple Dirac points under compression (up to −20% strain), with the number of these points commensurate with the number of tetra-carbon base-units along the width of the unit cell, accounting also for the mirror symmetry of the structure. Under tensile, uniaxial strain (up to 20% extension), the induced asymmetry in the carbon tetrabond results in the number of Dirac points being reduced, although a minimum number are preserved due to the fundamental mirror-symmetry of the symmetric ATGNR. Asymmetric ATGNRs, which are semiconductors, are shown to have tunable band-gaps that decrease as a function of increasing ribbon width and uniaxial strain. Uniaxial strain induces a single Dirac point at the band edge of these systems under high compression ( > 16%), with the closing of the band gap linked to symmetry-induced perturbations in the structure that override the symmetry-breaking, gap-opening mechanisms. In summary, the TB model shows ATGNRs to have suitable device features for flexible electronics applications, such as band-gap tuning, and for the strain engineering of relativistic properties.